2018
DOI: 10.1101/390179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-based ranking of cognitive domains to predict schizophrenia

Abstract: Schizophrenia is a devastating brain disorder that disturbs sensory perception, motor action, and abstract thought. Its clinical phenotype implies dysfunction of various mental domains, which has motivated a series of theories regarding the underlying pathophysiology. Aiming at a predictive benchmark of a catalogue of cognitive functions, we developed a bottom-up machine-learning strategy and provide a proof of principle in a multi-site clinical dataset (n=324). Existing neuroscientific knowledge on diverse co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 136 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…In this study, 10 of the 13 studies provided details of a validation process for the applied models 24,26,29,30,37–43,46,47 . Different forms of internal cross‐validation and holdout datasets were most commonly applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, 10 of the 13 studies provided details of a validation process for the applied models 24,26,29,30,37–43,46,47 . Different forms of internal cross‐validation and holdout datasets were most commonly applied.…”
Section: Resultsmentioning
confidence: 99%
“…Accuracy and sensitivity (recall)-specificity were the most frequently reported performance statistics (in 10 references 24,26,29,37,39,40,42,43,46,47 and 7 of studies, 24,26,38,40,42,46,47 respectively). Five of the studies 26,37,40,44,46 reported AUC, while Precision was reported by 2 studies.…”
Section: Predictive Model Performance Evaluation Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…ResNets with deeper layers have been shown to be more easily trainable than traditional DNNs with state-of-the-art results on benchmark tests (K. He et al, 2016). Stacking is an ensemble model averaging technique (Hastie et al, 2009) that we have used in our previous research (Karrer et al, 2019). Multiple base models can be used for separate classifications to then blend the results into a top-level, composite model for a final prediction.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…The prediction paradigm holds the promise of improving disease diagnosis, enhancing prognostic estimates, and ultimately paving the way to precision medicine (Brammer, 2009; Bzdok et al, 2021). Machine learning methods are now increasingly adopted for the goal of classifying various conditions, including autism spectrum disorder (ASD) (Heinsfeld et al, 2018; Plitt et al, 2015; Sabuncu et al, 2015; Wolfers et al, 2019), attention-deficit/hyperactivity disorder (ADHD) (Brown et al, 2012; Riaz et al, 2020; Sen et al, 2018; Wang et al, 2018), anxiety (ANX) (Frick et al, 2014; Liu et al, 2015), or schizophrenia (Davatzikos et al, 2005; Karrer et al, 2019; Rozycki et al, 2018; Shen et al, 2010; Yassin et al, 2020). However, there is a large variability in the accuracy reports across studies (Arbabshirani et al, 2017; Pulini et al, 2019; Woo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%